GRID CONNECTED SOLAR HYDROGEN ENERGY SYSTEM - Tjukup Marnoto (Eksergi, 2010)
Solar-Hydr-ogen energy system has been regarded æ ttre future energy system that is clean, environmental-friendly, availability of renewable energy resources and easy to transfer or deliver to the end user. The grid connected solar hydrogen energy system (GCSHES) have the capability of overcoming the problems that óccur on the grid connected power system (GCPS) when there is a black out of grid electricity. Moreover, stand alone power system (SAPS) requires batteries and larger hydrogen tank capacity is required for higher energy genèration. An experimental GCSHES has been setup and tested. The GCSHES consists of subsystems photovoltaic (PV) array with 40 PV module type multicrystalin with its capacity of 5000 Wp, inverter capacity of 6000 W, electrolyzer capacity of 19 scf/h, hydrogen tank capacity of 1500 liter and fuelcell of 500 W. The characteristics equation and maximuln power output of PV was presented The monthly efficiency and performance of PV array is 12.7% and 26% , while the efficiency and performance of inverter is 95.1% and 98%, respectively. The efficiency of electrolyzer subsystem and fuel cell is 51% and 25%, respectively. The techno economical analysis indictated that the pay back period of this system is 18 years.